Rationale, progress and development of vaccines utilizing STING-activating cyclic dinucleotide adjuvants. (November 2013) - Dubensky, Thomas W.; Kanne, David B.; Leong, Meredith L.
A principal barrier to the development of effective vaccines is the availability of adjuvants and formulations that can elicit both effector and long-lived memory CD4 and CD8 T cells. Cellular immunity is the presumptive immune correlate of protection against intracellular pathogens: a group composed of bacteria, viruses and protozoans that is responsible for a staggering level of morbidity and mortality on a global scale. T-cell immunity is also correlated with clinical benefit in cancer, and the development of therapeutic strategies to harness the immune system to treat diverse malignancies is currently undergoing a renaissance. Cyclic dinucleotides (CDNs) are ubiquitous small molecule second messengers synthesized by bacteria that regulate diverse processes and are a relatively new class of adjuvants that have been shown to increase vaccine potency. CDNs activate innate immunity by directly binding the endoplasmic reticulum-resident receptor STING (stimulator of interferon genes), activating a signaling pathway that induces the expression of interferon-β (IFN-β) and also nuclear factor-κB (NF-κB) dependent inflammatory cytokines. The STING signaling pathway has emerged as a central Toll-like receptor (TLR) independent mediator of host innate defense in response to sensing cytosolic nucleic acids, either through direct binding of CDNs secreted by bacteria, or, as shown recently, through binding of a structurally distinct CDN produced by a host cell receptor in response to binding cytosolic double-stranded (ds)DNA. Although this relatively new class of adjuvants has to date only been evaluated in mice, newly available CDN-STING cocrystal structures will likely intensify efforts in this field towards further development and evaluation in human trials both in preventive vaccine and immunotherapy settings.